2014
DOI: 10.1111/maec.12198
|View full text |Cite
|
Sign up to set email alerts
|

Temporal partitioning of microhabitat use among four juvenile fish species of the genusDiplodus(Pisces: Perciformes, Sparidae)

Abstract: Timing, microhabitat selection and behavior from the onset of settlement to recruitment to the adult population of juvenile fishes of the genus Diplodus (Pisces: Sparidae) were investigated along a rocky coastline in the Central Mediterranean Sea. The settlement periods in Diplodus sargus and Diplodus annularis were concentrated in spring, between late May and early June, and the recruits leave the nursery grounds in late September–October. Juvenile fishes of Diplodus puntazzo and Diplodus vulgaris showed a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 82 publications
3
31
0
Order By: Relevance
“…Juvenile Diplodus spp. are known to undergo ontogenic shifts in habitat use, enlarging their niche by vertical (for D. vulgaris ) or horizontal (for D. sargus ) migration (Ventura et al ). Those shifts have also been observed on the AH within harbors (Bouchoucha et al ), and during experiments, most juveniles were observed under the AH, which seems to be the same in situ (authors' unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile Diplodus spp. are known to undergo ontogenic shifts in habitat use, enlarging their niche by vertical (for D. vulgaris ) or horizontal (for D. sargus ) migration (Ventura et al ). Those shifts have also been observed on the AH within harbors (Bouchoucha et al ), and during experiments, most juveniles were observed under the AH, which seems to be the same in situ (authors' unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…From the orthomosaic generated by 160 overlapping images the high heterogeneity over the whole extent of the mapped area was clearly visible. Along this jagged coastline we identified two small coves (Figure 7a) were the presence of particular natural features such as sandy patches, pebbles and large boulders made such area suitable for settlement of juvenile sparid fish [42,65,66]. In fact, thanks to the high resolution (3 cm/pix) of the imagery after a visual inspection we were able to identify the most suitable habitats for juvenile fish of the genus Diplodus.…”
Section: Nursery Area Of Juvenile Fishmentioning
confidence: 90%
“…They are highly abundant in both natural and artificial rocky coastal areas (Tortonese 1965) and their juveniles are present in high abundances inside marinas, at least along the internal side of peripheral breakwaters (Clynick 2006). Natural settlement patterns are fairly well described for all four species: D. annularis, D. puntazzo and D. sargus all settle in one pulse, in June-July, October-November and May-June respectively, while D. vulgaris settles in two pulses, in November-December and in January-February, the first pulse being the more predominant (García-Rubies & Macpherson 1995, Harmelin-Vivien et al 1995, Cheminee et al 2011, Ventura et al 2014. In Diplodus species, physical habitat characteristics (substrate, depth, level of protection from the prevailing winds, etc.)…”
Section: Species Studiedmentioning
confidence: 93%